Silicon nanoparticles in higher plants: Uptake, action, stress tolerance, and crosstalk with phytohormones, antioxidants, and other signalling molecules. (1st October 2022) - Mukarram, Mohammad; Petrik, Peter; Mushtaq, Zeenat; Khan, M. Masroor A.; Gulfishan, Mohd; Lux, Alexander
Abstract: Silicon is absorbed as uncharged mono-silicic acid by plant roots through passive absorption of Lsi1, an influx transporter belonging to the aquaporin protein family. Lsi2 then actively effluxes silicon from root cells towards the xylem from where it is exported by Lsi6 for silicon distribution and accumulation to other parts. Recently, it was proposed that silicon nanoparticles (SiNPs) might share a similar route for their uptake and transport. SiNPs then initiate a cascade of morphophysiological adjustments that improve the plant physiology through regulating the expression of many photosynthetic genes and proteins along with photosystem I (PSI) and PSII assemblies. Subsequent improvement in photosynthetic performance and stomatal behaviour correspond to higher growth, development, and productivity. On many occasions, SiNPs have demonstrated a protective role during stressful environments by improving plant-water status, source-sink potential, reactive oxygen species (ROS) metabolism, and enzymatic profile. The present review comprehensively discusses the crop improvement potential of SiNPs stretching their role during optimal and abiotic stress conditions including salinity, drought, temperature, heavy metals, and ultraviolet (UV) radiation. Moreover, in the later section of this review, we offered the understanding that most of these upgrades can be explained by SiNPs intricate correspondence with phytohormones, antioxidants, and signalling molecules. SiNPs can modulate the endogenous phytohormones level such as abscisic acid (ABA), auxins (IAAs), cytokinins (CKs), ethylene (ET), gibberellins (GAs), and jasmonic acid (JA). Altered phytohormones level affects plant growth, development, and productivity at various organ and tissue levels. Similarly, SiNPs regulate the activities of catalase (CAT), ascorbate peroxidase (APX), superoxide dismutase (SOD), and ascorbate-glutathione (AsA-GSH) cycle leading to an upgraded defence system. At the cellular and subcellular levels, SiNPs crosstalk with various signalling molecules such as Ca 2+, K +, Na +, nitric oxide (NO), ROS, soluble sugars, and transcription factors (TFs) was also explained. Graphical abstract: Image 1